2015
DOI: 10.1038/srep18298
|View full text |Cite
|
Sign up to set email alerts
|

Highly Flexible and Conductive Printed Graphene for Wireless Wearable Communications Applications

Abstract: In this paper, we report highly conductive, highly flexible, light weight and low cost printed graphene for wireless wearable communications applications. As a proof of concept, printed graphene enabled transmission lines and antennas on paper substrates were designed, fabricated and characterized. To explore its potentials in wearable communications applications, mechanically flexible transmission lines and antennas under various bended cases were experimentally studied. The measurement results demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 39 publications
1
124
0
Order By: Relevance
“…Extrapolation to 25 mm or 1 mil thickness is common practice in the field, [23,38] but requires a linear dependence of conductivity with thickness which may not hold true for all processing conditions. In our case, up to the maximum achieved thicknesses of 12 mm a linear dependence is observed, so that extrapolation to 1 mil seems reasonable.…”
Section: Parametermentioning
confidence: 99%
“…Extrapolation to 25 mm or 1 mil thickness is common practice in the field, [23,38] but requires a linear dependence of conductivity with thickness which may not hold true for all processing conditions. In our case, up to the maximum achieved thicknesses of 12 mm a linear dependence is observed, so that extrapolation to 1 mil seems reasonable.…”
Section: Parametermentioning
confidence: 99%
“…These previous reports of ITO's disadavantages have given rise to a highly motivated search for ITO alternatives, and those efforts have focused on candidates including Ag nanowires (NWs), metalmeshes, carbon nanotubes (CNT) and graphenes, PEDOT:PSSs, and their hybrids. A great number of studies on those alternative materials have been conducted worldwide and promising results been reported in many cases [21][22][23][24]. For instance, it has been reported that Ag-NWs and metal-meshes exhibit very low R s (b100 Ω/sq) with moderate transmittance (N 80%) and high flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, we are using carbon based nanomaterials such as graphene [35], because it is a low-cost material with high carrier mobility, high elasticity, to elaborate nanodevices, applied to biomedicine [36]. We are interested in elaborating, by micro-nanofabrication techniques, graphene antennas to succeed in having a wider broadband [37,38] and to be able to use graphene in wearable devices [39] or as an antenna patch [40], which would represent an improvement in the proposed device, for the real time monitoring of children and people.…”
Section: Discussionmentioning
confidence: 99%